Appealing administrative decisions before the Federal Supreme Court Iraq - Turki Khalaf AL-Jburi, Issa (International Journal of Psychosocial Rehabilitation, 2020)
Control of the constitutionality of laws in the federal state is necessary and even inevitable. If there is no means to ensure that this distribution of jurisdiction is effective, which prevents states from overriding the jurisdiction of the central government and vice versa, the union cannot continue. And its federal constitution, with the corresponding adoption of those mandates by an independent constitution and the legislative authority of each of them resulting in duplication of laws and decisions. To emphasize the principle of the supremacy of the constitution, the need arose to determine the principle of constitutional control, Divorce at the present time, to ensure that all public authorities and constitutional rules for its occupation of the legal pyramid in the state directly at the terms of reference assigned to it. In addition to the administrative judiciary, Article (89) of the Constitution specifies the federal judicial authority which consists of (the Supreme Judicial Council and the Court), the judiciary, the judiciary, the judiciary, The Federal Supreme Court, the Federal Court of Cassation, the Public Prosecution Service, the Judicial Supervisory Commission and the other federal courts, which are organized in accordance with the law). The judicial system in Iraq is based on a pyramid at the top of the Federal Supreme Court. The second requirement is to monitor the constitutionality of administrative decisions under the Constitution of the Republic of Iraq for the year 2005